Allergic Contact Dermatitis Induced by Textile Necklace - Uffe Nygaard; Henrik Højgrav Kralund; Mette Sommerlund (Karger Publishers, 2013)
Allergic contact dermatitis to textile dyes is considered to be a rare phenomenon. A recent review reported a prevalence of contact allergy to disperse dyes between 0.4 and 6.7%. The relevance of positive patch testing was not reported in all studies. Textile dye allergy is easily overlooked and is furthermore challenging to investigate as textile dyes are not labelled on clothing. In this report, we present a case of allergic contact dermatitis to a textile necklace. The patch test showed strong reactions to the necklace and the azo dyes Disperse Orange 1 and Disperse Yellow 3. Despite the European legislation and the reduced use of disperse dyes in Third World countries, disperse azo dyes still induce new cases of allergic contact dermatitis.